Pendampingan Penyusunan Laporan Keuangan Berbasis PSAK EMKM Bagi Koperasi dan UMKM di Kota Batam di Tengah Pandemi Covid-19 - Dedi Kurniawan; Nanik Lestari; Hendra Gunawan; Sinarti Sinarti; Arif Darmawan; Wika Arsanti Putri; Adi Irawan Setiyanto; Danar Irianto; Muhammad Ramadhan Slamet; Muhammad Irsyad Halim; Alfonsa Dian Sumarna (Politeknik Negeri Batam, 2022)
Purpose: This community service activity has two objectives, namely, to carry out one of the tri dharma of higher education, namely community service through the implementation of knowledge held to the community and providing training and assistance in preparing financial reports to MSMEs in Batam City based on a standard. With this training and mentoring, it is expected that there will be an increase in the ability and transfer of knowledge in MSMEs. Benefits: Having been able to prepare financial reports according to standards can be one of the requirements for MSMEs to develop their business by submitting additional capital to third parties such as investors, banks, creditors and others. Then, this activity is expected to increase the activity of the community's economy and have implications for increasing family income in Batam City. Problems: The low ability of MSMEs in making financial reports based on accounting standards such as making reports of cash flow, profit and loss, and financial position. This problem becomes one of the obstacles for business to be sustainable. Methods: The service is carried out in three stages, namely, preparation, implementation, including information gathering, material preparation, material delivery, practice, monitoring, and evaluation, and reporting. In the midst of the current Covid-19 pandemic, it is not possible to conduct direct or face-to-face training and guidance, therefore these training and mentoring activities will be carried out online. The media used by WhatsApp and Zoom.